A case of hypoglossal nerve stimulator‐resistant obstructive sleep apnea cured with the addition of a chin strap. (7th December 2017) - Ramaswamy, Apoorva T.; Li, Carol; Suurna, Maria V.
Abstract : A population of appropriately selected patients does not respond, or does not achieve cure, with hypoglossal nerve stimulation (HGNS). We describe the case of nonresponder whose obstructive sleep apnea (OSA) resolved with the addition of chin strap. After initial placement and titration of HGNS implant, follow‐up sleep study demonstrated persistent moderate OSA. Drug‐induced sleep endoscopy demonstrated supraglottic collapse with activate neurostimulation. With mouth closure and change of stimulation settings to unipolar from bipolar, the airway collapse and desaturations improved. The follow‐up polysomnogram with (HGNS) therapy and chin strap demonstrated resolution of sleep apnea. Laryngoscope, 128:1727–1729, 2018